EFEKTIVITAS INTEGRASI PERMAINAN TRADISIONAL DALAM PEMBELAJARAN DI SEKOLAH: LITERATUR SISTEMATIS - Muhklisatun Intihana; Eko Handoyo; Hanafi Hussin; Indriana Eko Armaidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyzes the effectiveness of integrating traditional games in primary and secondary school learning based on recent research. A systematic literature review (SLR) applied to 20 scientific articles from Sinta and Scopus-indexed journals published between 2020 and 2025. Findings consistently indicate that integrating traditional games significantly increases student learning motivation (average improvement of 25–40%), cognitive abilities, social skills, and numeracy literacy. Additionally, traditional games are proven effective in developing student character, preserving local culture, and supporting active learning. Key barriers include limited time, insufficient teacher training, and inadequate facilities. These findings underscore the importance of curricula that accommodate traditional games as a local-wisdom-based pedagogical strategy.